Citra Destinasi : Pengaruhnya terhadap Kepuasan dan Loyalitas Wisatawan yang Berkunjung ke Gunung Bromo - Hidayatullah, Syarif; Windhyastiti, Irany; Patalo, Ryan Gerry; Rachmawati, Ike Kusdyah; Irany Windhyastiti (University of Merdeka Malang, 2020)
The purpose of this study is to determine the effect of destination images consisting of cognitive images, unique images and affective images on loyalty through visitor satisfaction at Mount Bromo natural tourism destinations. This type of research is explanatory research and data collection techniques through questionnaires. The sampling technique uses the purposive sampling technique with the characteristics of people who have been to Mount Bromo. The sample in this study amounted to 110 respondents. The analysis technique uses hypothesis testing and the two model multiple regression test. Results of research show that cognitive imagery, unique imagery and affective imagery have a significant effect on visitor satisfaction, furthermore cognitive imagery and affective imagery have a significant effect on visitor loyalty while unique images have no significant effect on visitor loyalty. If seen from the indirect effect, the results of cognitive image and unique image have a significant effect on loyalty through visitor satisfaction, while affective image does not affect loyalty through visitor satisfaction.https://doi.org/10.26905/jmdk.v8i1.4246